2018
DOI: 10.3961/jpmph.17.167
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Inequalities in the Incidence of Colorectal Cancer and Associated Factors in the Neighborhoods of Tehran, Iran: Bayesian Spatial Models

Abstract: ObjectivesThe aim of this study was to determine the factors associated with the spatial distribution of the incidence of colorectal cancer (CRC) in the neighborhoods of Tehran, Iran using Bayesian spatial models.MethodsThis ecological study was implemented in Tehran on the neighborhood level. Socioeconomic variables, risk factors, and health costs were extracted from the Equity Assessment Study conducted in Tehran. The data on CRC incidence were extracted from the Iranian population-based cancer registry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…We also found adenocarcinoma (91.53%) appeared to be the most common pathology followed by mucinosis (7.31%), which occurred in the second place. This finding is in line with surgery reference books [31]; indeed, 94% of tumors in the colon are predominantly adenocarcinoma [32,33]. The results of the present study suggest that most hospitalized stages III/IV CRC patients' post-surgery's 5-year survival rate typically ranged from a 90%, 70% and 10% for those encountered with localized, mild regional and sever distant metastasis, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…We also found adenocarcinoma (91.53%) appeared to be the most common pathology followed by mucinosis (7.31%), which occurred in the second place. This finding is in line with surgery reference books [31]; indeed, 94% of tumors in the colon are predominantly adenocarcinoma [32,33]. The results of the present study suggest that most hospitalized stages III/IV CRC patients' post-surgery's 5-year survival rate typically ranged from a 90%, 70% and 10% for those encountered with localized, mild regional and sever distant metastasis, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…There was a relationship between the regional disparity of obstetrics and gynecologic services with children and infants mortality rates in Iran (34), while regional disparities were proven to exist in the distribution of health care facilities in Iran (35). Spatially Rostami et al (36) also proved the existence of geographic disparity in fatal drug overdose cases, while Mansori et al (37) and Momenyan et al (38) found a spatial disparity. Mansori et al (37) detected disparity in the incidence of colorectal cancer case, and Momenyan et al (38) in HIV/AIDS cases mortality risk.…”
Section: Discussionmentioning
confidence: 95%
“…indeed, 94% of tumors in the colon are predominantly adenocarcinoma [32,33]. The results of the present study suggest that most patients referred to the hospital were in the stages III and IV CRC post-surgery survival is highly dependent upon the diagnosis stage, and typically ranges from a 90% of 5-year survival rate for CRCs detected at the localized stage; 70% for regional to 10% for people diagnosed for distant metastatic CRC.…”
Section: Discussionmentioning
confidence: 68%